Comparing the efficiency of pure and mixed cationic and nonionic surfactants used in enhanced oil recovery by mesoscopic simulations. (1st October 2020) - Bustamante-Rendón, R.A.; Pérez, E.; Gama Goicochea, A.
Graphical abstract: Abstract: The decrease of the interfacial tension between water and oil by addition of nonionic and cationic surfactants known to be optimal for enhanced oil recovery is studied here using dissipative particle dynamics numerical simulations. Three nonionic surfactants are modeled: Neodol nonylphenol ethoxylate, Neodol Propoxate, and nonylphenol ethoxylate, and the cationic dodecyl trimethyl ammonium bromide (DTAB). To model DTAB accurately the electrostatic interactions are included explicitly. The interfacial tension is calculated as a function of surfactant concentration, at constant temperature and volume. DTAB is found to be more efficient in lowering the interfacial tension than the nonionic surfactants, at the same concentration. Our simulations show that their different performance is due to their adsorption mechanisms at the interface. The nonionic surfactants adsorb mostly as monolayers, while DTAB adsorbs in multilayers. An equation for the interfacial tension as a function of surfactant concentration equivalent to Szyszkowski's equation is proposed for multilayer adsorption at the water-oil interface. The two – dimensional potentials of mean force calculated at the water-oil interface reveal a homogeneous interface when DTAB is present. This is in contrast with the nonionic surfactants, whose potentials of mean force show separate regions of hydrophobic and hydrophilic regions at the interface. Lastly, synergistic combinations of the cationic and nonionic surfactants are tested, yielding optimal mixtures that can reduce more the interfacial tension at lower surfactant concentrations. It is argued that our conclusions are useful to researchers designing new surfactants not only for enhanced oil recovery but also for other soft matter applications.